Data Privacy Concerns and User Trust in Indonesia’s Fintech Ecosystem - Apriyanto Apriyanto; Adih Supriadi (Eastasouth Institute, 2026)
The rapid expansion of the financial technology (fintech) ecosystem in Indonesia has transformed the delivery of financial services by improving accessibility, efficiency, and convenience. However, increasing reliance on digital financial platforms has also raised concerns regarding personal data protection, application usability, and user confidence. This study aims to examine the influence of data privacy issues and application usability on user trust within the Indonesian fintech ecosystem. A quantitative research approach was employed using survey data collected from 125 fintech users in Indonesia through a structured questionnaire measured with a five-point Likert scale. The collected data were analyzed using Statistical Package for the Social Sciences (SPSS) version 25, including validity testing, reliability testing, classical assumption testing, multiple linear regression analysis, t-test, F-test, and coefficient of determination analysis. The findings indicate that both data privacy issues and application usability have a positive and significant effect on user trust. The regression results demonstrate that application usability has a stronger influence on user trust compared with data privacy protection, indicating that user experience, ease of interaction, and system reliability are critical factors in building confidence toward fintech services. Furthermore, the model explains 58.7% of the variance in user trust, confirming that privacy management and usability are important determinants of fintech acceptance and continued usage. This study highlights the importance for fintech providers to integrate robust data protection mechanisms with user-centered application design to develop secure, reliable, and sustainable digital financial services in Indonesia.